An E-healthcare system to prevent the renal disease of diabetic patients belonging to Peri-urban areas of large cities - Nieto Chaupis, Huber (2016)
We have performed computational simulations aimed to evaluate the impact of an ehealth system in order to keep the stability of the diabetic patients belonging to Peri-urban areas of large cities. In concrete, this study is focused in one of the main causes of mortality in diabetic patients: the renal disease, which might decrease their quality of life gradually. Basically, the synergy between the teleconsults and medical visits might delay the progress of diabetes through a plan of monitoring using text messages, glucose test, and urine samples. From a sample of 25 patients, we modeled the possible scenarios of complications due to factors which are entirely derived from the behavior of patient. Under the assumption that no any ehealth system is working, we have found that at least NR/ND = 5/25 patients might acquire renal complications, in contrast to the case when the system is operating: NR/ND = 2/25 might have a high probability for acquiring the renal damage, which means that the ehealth system would reduce the number of patients with serious complications in up to a 40%.